Research in Management Information Systems: The Minnesota Experiments - Dickson, Gary W.; Senn, James A.; Chervany, Norman L. (Management Science, 1977)
The use of computer based information-decision systems to support decision making in organizations has increased significantly in the last decade. Very little effort has been devoted, however, to determine what relationships exist between the structure of information presented for decision making and the ensuing effectiveness of the decision. This article summarizes a series of experiments. The Minnesota Experiments, which were conducted to examine the significance of various information system characteristics on decision activity. Several research programs administered in the period 1970–1975 are discussed in this paper. By varying the manner in which information was provided to participants in each experiment, the impact of various information system characteristics and individual differences on decision effectiveness was investigated. Analysis of the results shows that, in many cases, the decisions/decision-making process of the participants was affected by the information system structure and/or attributes of individual decision makers. The results suggest guidelines for the designers of information systems and fruitful avenues for continued research.